Modifiable factors associated with patient-reported pain during and after screening colonoscopy - Bugajski, Marek; Wieszczy, Paulina; Hoff, Geir; Rupinski, Maciej; Regula, Jaroslaw; Kaminski, Michal Filip (Gut, 2018)
Objective Pain associated with colonoscopy is a major burden for patients. We investigated modifiable factors associated with patient-reported pain during and after colonoscopy. Design This cross-sectional analysis included database records from 23 centres participating in a population-based colonoscopy screening programme in Poland. Colonoscopies were performed under three sedation modalities: none, benzodiazepine-opioid sedation or propofol sedation. We used Gastronet (a validated tool) to assess patients’ pain during and after colonoscopy; pain was scored on a four-point scale (no, little, moderate or severe pain), with moderate to severe defined as painful. We used multivariate logistic regression models to estimate ORs for painful colonoscopy and calculated risk-adjusted ratios of painful colonoscopies per endoscopist and compared it to the mean rate. Results Of 35 216 screening colonoscopies in 2014 and 2015 included in our study, 22 725 (64.5%) patients returned valid Gastronet questionnaires. The proportion of examinations described as causing pain during (after) the procedure was 22.5% (14.2%) for unsedated, 19.9% (13.5%) for benzodiazepine-opioid sedation and 2.5% (7.5%) for propofol sedation. Propofol sedation, higher case volume of endoscopists, newest endoscope generation and adequate bowel preparation were significantly associated with lower odds of painful colonoscopy. Pain scores after colonoscopy showed similar associations. Adjusted pain rates during and after colonoscopy varied 11 and over 23-fold, respectively, between endoscopists. Conclusion We identified several independent, modifiable factors associated with pain during and after colonoscopy, of which individual endoscopist was the most important. Dedicated training should be considered to decrease variability among endoscopists.